2021
DOI: 10.11646/zootaxa.5027.3.7
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Myxia (Hemiptera: Auchenorrhyncha: Cixiidae) collected on palms from the Reserva Privada el Silencio de Los Angeles Cloud Forest in Costa Rica

Abstract: A new species of Myxia Bahder & Bartlett (Cixiidae: Cixiinae: Oecleini) is established as Myxia hernandezi sp. n. collected from native palms in cloud forest habitat in Costa Rica. Placement in the genus Myxia is supported by molecular analysis of the cytochrome c oxidase subunit I (COI) and 18S loci as well as morphological characters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Oecleus mackaspringi Myrie et al, 2019(Myrie et al 2019 In other oecleinian taxa a normal pattern is observed in Haplaxius dougwalshi Bahder et al, 2020, (Bahder et al 2020) and H. pococo Bahder & Bartlett, 2021 (Barrantes Barrantes et al 2021b), in the genus Bothriocera Burmeister, 1835, the amber fossil Bothriobaltia Szwedo, 2002(Szwedo, 2002, Oecleus Stål, 1862 (Ball and Klingenberg 1935) and Borbonomyndus Attié, Bourgoin & Bonfils, 2002(Attié et al 2002. In Meenocixius Attié, Bourgoin & Bonfils, 2002(Attié et al 2002 an unusual late forkings of MP 1+2 and MP 3+4 at the submarginal line in a 4-terminal MP is observed.…”
Section: Forewing Venationmentioning
confidence: 98%
“…Oecleus mackaspringi Myrie et al, 2019(Myrie et al 2019 In other oecleinian taxa a normal pattern is observed in Haplaxius dougwalshi Bahder et al, 2020, (Bahder et al 2020) and H. pococo Bahder & Bartlett, 2021 (Barrantes Barrantes et al 2021b), in the genus Bothriocera Burmeister, 1835, the amber fossil Bothriobaltia Szwedo, 2002(Szwedo, 2002, Oecleus Stål, 1862 (Ball and Klingenberg 1935) and Borbonomyndus Attié, Bourgoin & Bonfils, 2002(Attié et al 2002. In Meenocixius Attié, Bourgoin & Bonfils, 2002(Attié et al 2002 an unusual late forkings of MP 1+2 and MP 3+4 at the submarginal line in a 4-terminal MP is observed.…”
Section: Forewing Venationmentioning
confidence: 98%
“…Recent surveys of planthoppers associated with palms in Costa Rica has led (so far) to the description of 14 new species, including five oecleine cixiids (two Haplaxius Fowler, three Myxia Bahder & Bahder et al 2019aBahder et al , 2020aBarrantes et al 2021;Echavarria et al 2021aEchavarria et al , 2021b; eight cenchreine derbids (in five genera; Bahder et al 2019bBahder et al , 2020bBahder et al , 2020cBahder et al , 2021aBahder et al 2020bBahder et al , 2020cEchavarria et al 2021c) and one otiocerine derbid (Anotia Kirby; Barrantes et al 2020). The impetus for this survey activity is a renewed interest in the epidemiology of palm lethal decline phytoplasmas and their putative vectors in Florida and the Caribbean basin.…”
Section: Introductionmentioning
confidence: 99%